THE CORRELATION OF SMOKING HABITS TO THE LEVEL OF PHYSICAL FITNESS AND LEARNING OUTCOMES ON STUDENTS OF PJKR FKIP UNTAD BATCH 2018 - Muhammad Ismail; Andi Sultan Brilin S.E.Wahyudhi (Universitas Tadulako, 2021)
The problems in this study are: a) Is there a relationship between smoking habits and the level of physical fitness of the students of PJKR FKIP UNTAD class of 2018? ; b) Is there a relationship between smoking habits and learning outcomes among PJKR FKIP UNTAD students class 2018? This study aims to: a) determine whether there is a relationship between smoking habits and the level of physical fitness of students of PJKR FKIP UNTAD class of 2018; b) determine whether there is a relationship between smoking habits and learning outcomes in students of PJKR FKIP UNTAD class of 2018. This type of research is correlational research. The data collection technique used a questionnaire, beep test, and the sample GPA value. The number of samples in this study were 26 students. The data analysis technique uses the SPSS 20 application. The results of this study indicate: a) There is no relationship between smoking habits and physical fitness levels in students of PJKR FKIP UNTAD class of 2018; b) There is no relationship between smoking habits and learning outcomes in students of PJKR FKIP UNTAD class of 2018